Implementasi Augmented Reality pada Produk Laptop sebagai Media Promosi Berbasis Android - Yusuf Wahyu Setiya Putra; Andre Kurniawan (J I M P - Jurnal Informatika Merdeka Pasuruan, 2021)
The benefits of technology at this time have greatly affected human life, with the creation of sophisticated machines or tools used by humans to achieve human needs. In line with these developments, augmented reality technology emerged or commonly referred to as Augmented reality (AR). Augmented reality is an environment that incorporates 3D virtual objects into the real environment. The purpose of this study is to implement an augmented reality application that can help buyers who have difficulty checking laptop specifications at the Focus display computer store. Some of the laptops provided have no specifications listed, so this causes buyers to be confused about the specifications of the laptop. This augmented reality application was created using the blender application software as an application to create 3D models, unity 3D software as an application to create augmented reality and build it to android, corel draw software as an application to create assets, and vuforia which is used to create augmented reality target images. Image targets made in the form of brochures and qr code to display objects and laptop specifications.Keywords— Augmented reality,blender, vuforia, corel draw, unity 3D.